A framework for social and environmental accounting research. Issue 3 (September 2017) - Lehman, Glen; Kuruppu, Sanjaya Chinthana
Abstract: This essay explores recent trends in social and environmental accounting research (SEAR). We offer a basic SEAR typology to examine the limitations and possibilities within the current discourse. SEAR has taken a corporate approach in liberal democratic social space. Our typology examines the opportunities for SEAR to interpret and create change in social practice.